Corrido in Preisker Park - Manuel Echavarria::::::photographer:::
David Sanchez, a Santa Maria resident and Cal Poly Education professor takes a rest after performing a Corrido, a Mexican ballad, in Preisker Park in Santa Maria during a UFW Rally. Sanchez was a strong UFW supporter and an advocate for educational equity in San Luis Obispo and Santa Barbara Counties. David Sánchez, un residente de Santa Maria y profesor de Educación en Cal Poly, toma un receso después de cantar un corrido en el parque Preisker en Santa Maria durante una reunión de la UFW. Sánchez era un fuerte partidario de la UFW y también apoyaba la egalidad en la educación en los municipios de San Luis Obispo y Santa Barbara.